Stored products mites in cheese ripening: Health aspects, technological and regulatory challenges in Brazil. (March 2018) - Carvalho, Michelle M.; Oliveira, Eugenio E.; Matioli, Andre L.; Ferreira, Célia L.L.; Machado da Silva, Norma; De Dea Lindner, Juliano
Abstract: Stored products mites have been reported in the literature either as a problem (e.g., causing significant economic losses and reducing quality) or as food technology coadjuvants (e.g., providing specific and desirable flavor characteristics to certain cheese types). Stored products mites infestations usually occur in cheeses that need long ripening periods. Effective controls of such infestations have been achieved by implementing good manufacturing practices (GMP) rather than by synthetic or botanical miticides. Although the effects caused by cheese mites during storage may be undesirable in some types of cheese, in certain circumstances, these mites are essential to the production of other types of cheeses (Mimolette and Milbenkäse cheeses). There is a gap of information on the risk status of consumption of mite-containing cheese. Despite this lack of information, the production of mite-containing cheeses has gained new adepts in Brazil. Thus, this study has attempted to summarize the available taxonomic identity of known mite-containing cheeses and possible health problems related to the consumption of the mites associated with these cheeses. Furthermore, the present review also describes the technological challenges and regulatory aspects involved in the production of these cheese types, which can help the Brazilian mite-containing cheese production. Highlights: Mites that infest cheeses may be used as a ripening coadjuvant. Mite-containing cheese production is still empirical in Brazil without regulatory acts to guide their use. Identification of endogenous mites in Brazil must be applied to corroborate defining allowed species and ripening period. Risk assessment studies associated with mite-containing cheese consumption need to be addressed in the world.